Manual de producción de pimentón bajo invernadero - Casilimas, Héctor; Monsalve, Oscar; Bojacá, Carlos R.; Gil, Rodrigo; Villagrán, Edwin; Arias, Luis Alejandro; Fuentes, Luz Stella (Universidad Jorge Tadeo Lozano, 2012)
Pimentón-Capsicum annuum